Analisis Retorika Aristoteles Pidato Retno Marsudi pada Sidang Darurat Istimewa Ke-10 Majelis Umum PBB - Rayhan, Muhammad (Indonesian Journal of Applied Linguistics Review, 2024)
This study analyzes Indonesian Foreign Minister Retno Marsudi's speech at the 10th Special Emergency Session of the UN General Assembly in New York, 26 October 2023, using Aristotle's rhetorical theory which includes logos, ethos, and pathos. This research aims to identify the rhetorical strategies used and assess the effectiveness of the speech in achieving Indonesia's diplomatic goals amid complex global issues. The research method used is content analysis-based qualitative analysis of the text and video of the speech as well as supporting literature. The results showed that Retno Marsudi effectively utilized the logos element through data-based arguments and references to international resolutions, the ethos element through her credibility as an experienced diplomat, and the pathos element through emotional narratives about the humanitarian impact of global conflicts. The combination of the three elements strengthened Indonesia's diplomatic message and increased international audience acceptance. This research contributes to the study of rhetoric in diplomatic communication and provides practical insights for the development of more effective international communication strategies.